Training through the Utilization of Ginger into Syrup Products for the Community in Padukuhan Wirik, Gunungkidul Regency - Kurnianingtyas, Chandra Dewi (Lembaga Penelitian dan Pengabdian pada Masyarakat, 2023)
Ginger is one of the natural products in Padukuhan Wirik, Umbulrejo Village, Ponjong District, Gunungkidul Regency, which is widely grown in family medicinal plants. This training activity aims to provide new ideas for the community to do business and build MSMEs. In addition, this activity is also intended to increase the utilization of ginger into a more value-added and marketable product, namely ginger syrup. The method used was explaining the material, making ginger syrup, and discussing the question and answer. The audience of this activity was 35 PKK women in Wirik hamlet. This training activity succeeded in increasing the knowledge and skills of PKK women in processing ginger into syrup. The results of empowerment found that participants actively asked questions and practised the process of making ginger syrup. In line with the program, the PKK women of Wirik hamlet are interested in implementing the business idea of utilizing ginger in ginger syrup products to improve the family economy.